To strive is human, to abuse malign: discrimination and non-accidental violence of professional athletes without employee-style statutory protection - Roberts, V. L.; Sojo, V. E. (British Journal of Sports Medicine, 2020)
A recent judgement from a landmark employment case against British Cycling and UK Sport found that Jess Varnish, a former professional British cyclist, was neither an employee nor a worker of either organisation within the meaning of the Employment Rights Act 1996 or the Equality Act 2010. The relationship between the cyclist and British Cycling was judged to be more akin to a relationship between a student and a University (eg, service provider), and that funding provided to the cyclist by UK Sport was analogous to a grant.1